2006
DOI: 10.23818/limn.25.01
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter processing in low order streams

Abstract: Forests produce a large amount of detritus, that inevitably end up in streams, subsidizing aquatic systems with organic matter and nutrients. Here we review some of the research carried out at the University of Coimbra with the objective of getting a better understanding of the breakdown process of these materials and its incorporation to secondary production. Litter-fall in deciduous forests in Central Portugal can reach up to 750 g AFDM of leaves m -2 yr -1 , with 73% of the litter produced between October a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…4a) were needed to maintain the estimated leaf litter contribution to ER. This range is comparable to results from field studies in temperate streams reporting leaf litter standing stocks of as low as 4 g of ash free dry mass (AFDM) m À2 (Sycamore Creek, Sonoran Desert, Wallace et al 1999) and up to 450 g AFDM m À2 (deciduous forest streams in Portugal, Graça and Canhoto 2006). Direct observation in one of the study sites, Walker Branch, allowed a more refined assessment of the model results and confirmed that model estimates of leaf litter-related respiration for this site are reasonable.…”
Section: Respiration Dynamicssupporting
confidence: 83%
“…4a) were needed to maintain the estimated leaf litter contribution to ER. This range is comparable to results from field studies in temperate streams reporting leaf litter standing stocks of as low as 4 g of ash free dry mass (AFDM) m À2 (Sycamore Creek, Sonoran Desert, Wallace et al 1999) and up to 450 g AFDM m À2 (deciduous forest streams in Portugal, Graça and Canhoto 2006). Direct observation in one of the study sites, Walker Branch, allowed a more refined assessment of the model results and confirmed that model estimates of leaf litter-related respiration for this site are reasonable.…”
Section: Respiration Dynamicssupporting
confidence: 83%
“…In forest streams, the plant matter supplied by the riparian vegetation (e.g., leaves, wood) represents a major source of organic carbon for aquatic food webs [5]. In these ecosystems, plant litter decomposition is a fundamental ecosystem process mediated by the activities of microbes, namely fungi and bacteria, and invertebrate detritivores [6]. Fungi, particularly aquatic hyphomycetes, and bacteria produce a large variety of extracellular enzymes that promote leaf maceration and increase leaf palatability to invertebrate detritivores [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In these ecosystems, plant litter decomposition is a fundamental ecosystem process mediated by the activities of microbes, namely fungi and bacteria, and invertebrate detritivores [6]. Fungi, particularly aquatic hyphomycetes, and bacteria produce a large variety of extracellular enzymes that promote leaf maceration and increase leaf palatability to invertebrate detritivores [6,7]. Aquatic hyphomycetes are key decomposers of litter particularly in the initial stages of the process, while bacteria only increase their contribution when litter has been partially…”
Section: Introductionmentioning
confidence: 99%
“…It appears headwaters created more favorable environments for consumer-resource interactions to develop. The decrease in stream width and discharge may increase retention time for leaves (Graça and Canhoto 2006) and possibly promote consumer mobility (Gjerløv et. al.…”
Section: Discussionmentioning
confidence: 99%